The physiological costs of wearing respiratory protective devices : a thesis in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University - Laird, Ian Stewart; Laird, Ian Stewart (Massey University, 1995)
This thesis is concerned with the use of respiratory protective devices in New Zealand industry and the physiological costs the respirator imposes on the wearer. Two cross sectional surveys of respirator users were undertaken to determine the extent and nature of use or non-use in the working environment and which factors contribute most to non-use. Evidence is presented that indicated that non-use is common (50% of those surveyed) and that difficulty breathing, thermal discomfort and difficulty communicating and seeing were all important reasons for non-use. In addition, it was found that respirators are worn for extended lengths of time and that many users believe that their work when wearing a respirator was physically demanding. Evidence is presented that this is not the case. The physical characteristics of respiratory protection in terms of resistance to airflow, weights and dead space volumes, were measured in a selection of commonly used respirators in NZ industry. It was evident that most pressure-flow relationships were below recommended limits for inspiratory and expiratory resistances and that some masks in particular, offered little external resistance to breathing. The physiological consequences of wearing respirators was examined in a series of studies measuring relationships in heart rate, oxygen consumption, ventilation, facial skin temperatures and perceived exertion, with and with-out subjects wearing respirators and at differing levels of external work. It was found that the respirator imposed little physiological strain (in terms of heart rate, gas exchange and minute ventilation), but that psycho-physiological sensations (perceived difficulty breathing and rated perceived exertion) increased significantly. In addition, increases in facial skin temperatures, particularly the lip temperature under the mask when worn, caused a sensation of thermal discomfort that may be the predominant cue that influences reasons for non-use. Finally, the incongruence between physiological and psychophysiological measures of distress was clearly demonstrated in this thesis. It is apparent that not only is a respirator a complex device, but the micro-climate it produces on the skin surface and the effect this has on an individuals' perception of discomfort, is also enigmatic.
Keywords: Respirators; Breathing apparatus; Physiological effects; Safety equipment